Twenty‐five essential research questions to inform the protection and restoration of freshwater biodiversity - Harper, Meagan; Mejbel, Hebah S.; Longert, Dylan; Abell, Robin; Beard, T. Douglas; Bennett, Joseph R.; Carlson, Stephanie M.; Darwall, William; Dell, Anthony; Domisch, Sami; Dudgeon, David; Freyhof, Jörg; et al. (Aquatic conservation, 2021)
Freshwater biodiversity is declining at an unprecedented rate. Freshwater conservationists and environmental managers have enough evidence to demonstrate that action must not be delayed but have insufficient evidence to identify those actions that will be most effective in reversing the current trend. Here, the focus is on identifying essential research topics that, if addressed, will contribute directly to restoring freshwater biodiversity through supporting ‘bending the curve’ actions (i.e. those actions leading to the recovery of freshwater biodiversity, not simply deceleration of the current downward trend). The global freshwater research and management community was asked to identify unanswered research questions that could address knowledge gaps and barriers associated with ‘bending the curve’ actions. The resulting list was refined into six themes and 25 questions. Although context‐dependent and potentially limited in global reach, six overarching themes were identified: (i) learning from successes and failures; (ii) improving current practices; (iii) balancing resource needs; (iv) rethinking built environments; (v) reforming policy and investments; and (vi) enabling transformative change. Bold, efficient, science‐based actions are necessary to reverse biodiversity loss. We believe that conservation actions will be most effective when supported by sound evidence, and that research and action must complement one another. These questions are intended to guide global freshwater researchers and conservation practitioners, identify key projects and signal research needs to funders and governments. Our questions can act as springboards for multidisciplinary and multisectoral collaborations that will improve the management and restoration of freshwater biodiversity.